Wind turbine syndrome : a communicated disease - Chapman, Simon, 1951-; Crichton, Fiona (Public and social policy series., 2017)
As governments around the world look for ways to curb fossil fuel emissions, more and more countries are adopting renewable energy sources. Wind power is one of the cheapest sources of renewable energy, and windfarms are often looked to as a solution.